2010
DOI: 10.1016/s0026-0576(10)80037-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of black anodic films on 7175 aluminium alloy for space applications

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is a publisher-deposited version published in: http://oatao.univ-toulouse.fr/ Eprints ID: 4371To link to this article:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A previous study (Goueffon et al, 2009b) showed that films with initial porosities of 40% and 50% were crazed after colouring and sealing steps. Actually, the differential thermal dilatations in the sealing bath, associated to a poor limit tensile stress of highly porous films, were proved to lead to formation of cracks perpendicular to the interface during the process.…”
Section: Process Of Black Anodizingmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study (Goueffon et al, 2009b) showed that films with initial porosities of 40% and 50% were crazed after colouring and sealing steps. Actually, the differential thermal dilatations in the sealing bath, associated to a poor limit tensile stress of highly porous films, were proved to lead to formation of cracks perpendicular to the interface during the process.…”
Section: Process Of Black Anodizingmentioning
confidence: 96%
“…As the anodic films elaborated at 20 and 25°C (40% and 50% initial porosity) are crazed after the whole black anodizing process (Goueffon et al, 2009b), a finite element simulation was used to evaluate mechanical behaviour of a crazed thin film on its substrate during thermal cycling. The software SAMCEF was used to perform isotropic thermo-elastic calculations with 2-dimensional plane strain hypotheses.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to attractive combinations of (relatively) high strength and low density, 7000 series aluminium alloys (such as the 7175-T7351 alloy considered in the present work) have numerous naval, aerospace, and military applications [4][5][6] and have consequently received a great deal of attention in the literature. In the work of Benoit et al, for example, the microstructure of two 7000 series alloys was analysed, in addition to fundamental mechanical response parameters such as yield stress, ultimate tensile strength, elongation at fracture, and fracture initiation energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Linear relationships could however be recovered when dislocation spacing is considered in formulations. Goueffon and co-workers examined coefficients of thermal expansion in anodised 7175 films for space applications using 10mm thick beam bending experiments (values of 13.0+/-1.0x10 -6 K -1 were suggested [6]), with values being relatively independent of the porosity of the film [11].…”
Section: Introductionmentioning
confidence: 99%